Irish novelists and the Victorian age - Murphy, James H. (Oxford : Oxford University Press, 2011)
This text is a comprehensive study of fiction written by Irish authors during the Victorian age. James Murphy analyses the development of the novel in Ireland and examines the work of authors including William Carleton, Charles Lever, Somerville and Ross, and Bram Stoker in the social and literary contexts of their times.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: English fiction -- Irish authors -- History and criticism; English fiction -- 19th century -- History and criticism; Literature and society -- Ireland -- History -- 19th century